A methodology for enabling the sustainable development of Therapeutic tourism in the Egyptian desert – An applied study on the hamra ecolodge resort in Wadi El- Natroun –: منهجية تمكين التنمية المستدامة للسياحة العلاجية لصحراء مصر - Ahmed Ali Soliman Elsamahy, Nanees Abd Elhamid Elsayyad, Usama Mohamed Elfiky (Journal of engineering sciences and information technology, 2021)
Despite the importance of therapeutic tourism, it faces great obstacles that limit the growth of the sustainability of its development, among the main obstacles that stand in the way of sustaining the development of therapeutic tourism in Wadi El- Natroun is the existence of an urban phenomenon that did not follow sustainable development in its design, with the absence of coordination between the ministries and relevant bodies. It is the absence of specific mechanisms and methodology for how to choose the most important criteria and sustainable planning indicators to assess the sustainability of therapeutic resorts, as it is considered one of the most important pillars of development for the sustainability of therapeutic tourism, in order to preserve the therapeutic area’s resources from pollution resulting from human use, both in construction and operation In this way. The research provides a clearer picture for enabling the sustainable development of therapeutic tourism in Wadi El- Natroun through the preparation of a methodology and guidebook to enhance the sustainability of therapeutic tourism resorts in the region and their application in way that enables development decision- makers in the region to make rational and logical decisions regarding enabling sustainable development for therapeutic tourism development in it. And through both parts of theoretical research and analysis of the current situation in the study area, the most important results were reached the conclusion of a methodology and a guideline of the most important controls, determinants and sustainability indicators. It contains three criteria with eighteen basic determinants and eighty- one main indicators with the value of indicative relative weights divided as follows: Indicators of planning and design standards with a value of (40%)- Environmental standards indicators with a value of (35%)- Administrative and societal standards indicators with a value of (25%) , that are Serve as a checklist for developers and investors when preparing therapeutic tourism resorts in the design, management and operation processes to enable the sustainability of the development of desert therapeutic tourism on the site.The research ends with a set of recommendations, the most important of which is the need to apply the methodology and guidebook to therapeutic tourism resorts that are being prepared for in the region, it is considered one of the most important decision- making tools when planning to develop sustainable therapeutic tourism in the study area.